Gestational Weight Gain Among Military Members and Dependents. (2nd July 2016) - Krukowski, Rebecca A.; Bursac, Zoran; Linde, Brittany D.; Talcott, G. Wayne; Tedford, Eric; Klesges, Robert C.
ABSTRACT: Background: Given the escalating obesity rates among TRICARE beneficiaries and the negative health implications of excessive GWG, we examined GWG by body mass index (BMI) category and the prevalence of excessive GWG among these beneficiaries.Methods: In 2000-2012, 293 TRICARE beneficiaries gave birth to a single, live, and full-term infant and completed the Arkansas Pregnancy Risk Assessment Monitoring System questions about GWG gain and prepregnancy weight status. A 1:2 propensity score match of cases to controls was performed.Results: Mean GWG in TRICARE recipients (13.9 kg) was not significantly different from matched controls (14.3 kg). Forty-four percent of TRICARE beneficiaries gained in excess of the Institute of Medicine's GWG guidelines, which was similar to the rates among the matched controls (47%).Conclusions: These results can inform efforts to promote healthy GWG among TRICARE beneficiaries (e.g., health care provider-patient communications, behavioral interventions).